Screening to Identify Postoperative Pain and Cross‐Sectional Associations Between Factors Identified in This Process With Pain and Function, Three Months After Total Knee Replacement. Issue 5 (16th March 2022) - Wylde, Vikki; Sanderson, Emily; Peters, Tim J.; Bertram, Wendy; Howells, Nicholas; Bruce, Julie; Eccleston, Christopher; Gooberman‐Hill, Rachael
Abstract : Objective: To describe the screening and recruitment process of a randomized trial and evaluate associations with knee pain and function 3 months after total knee replacement (TKR). Methods: In order to screen for a multicenter trial, a total of 5, 036 patients were sent the Oxford Knee Score (OKS) questionnaire 10 weeks post‐TKR. Patients who reported pain in their replaced knee (score of ≤14 on the OKS pain component) completed a second OKS questionnaire 12 weeks post‐TKR. Those patients who were still experiencing pain 12 weeks post‐TKR completed a detailed questionnaire 13 weeks post‐TKR. These data were used to characterize pain in a cross‐sectional analysis. Multivariable regression was performed in order to identify factors associated with pain and function at 13 weeks post‐TKR. Results: We received OKS questionnaires from 3, 058 of 5, 063 TKR patients (60%), and 907 of the 3, 058 (30%) reported pain in their replaced knee 10 weeks post‐TKR. By 12 weeks, 179 of 553 patients (32%) reported improved pain (score of >14 on the OKS pain component). At 13 weeks, 192 of 363 patients (53%) who completed a detailed questionnaire reported neuropathic pain, 94 of 362 (26%) reported depression symptoms, and 95 of 363 (26%) anxiety symptoms. More severe pain at 13 weeks postoperatively was associated with poorer general health, poorer physical health, more pain worry, and lower satisfaction with surgery outcome. More severe functional limitation was associated with higher levels of depression, more pain worry, lower satisfaction with surgery outcome, and higher pain acceptance. Conclusion: Screening after TKR identified individuals with pain. We identified several potential targets (physical and mental health outcomes, acceptance of pain, and quality of life) for tailored intervention to improve outcomes for patients. Future trials of multidisciplinary interventions warranted.